Estimation of intake and quantification of hemoglobin adducts of acrylamide in adolescents in Sweden - Vryonidis, Efstathios; Törnqvist, Margareta; Lignell, Sanna; Rosén, Johan; Aasa, Jenny (Frontiers in Nutrition, 2024)
Blood samples (n=600) from participants in the Swedish dietary survey Riksmaten Adolescents 2016-17 were analysed with respect to haemoglobin (Hb) adducts from acrylamide (AA) and its metabolite glycidamide (GA) as biomarkers of internal dose/exposure. The results are presented from statistical analyses of food consumption data (two-day dietary recall and questionnaires) and measured Hb adduct levels.The estimated exposure as well as consumption data were examined in relation to non-dietary factors such as sex, age (group medians 12, 15 and 18 years), place of residence (urban/rural), smoking status, and parental education level.The median AA adduct level was estimated to 34 pmol/g Hb (range: 14-225). No significant difference was found for place of residence, parental education, sex or age. Significant difference was found between the median adduct levels of daily smokers (n=8) and never smokers (n=323) in the older age groups, but not between occasional smokers (n=47) and never smokers. The median differences between daily smokers and never smokers were 76, 40, and 128 pmol/g Hb for AA, GA, and AA+GA, respectively.The median AA intake for the whole group of adolescents, as estimated from dietary recall data combined with reported concentrations in food, was 0.40 µg/kg bw and day. The corresponding median intake estimated from measured Hb adduct levels of AA was 0.20 µg/kg bw and day. A significant, although low, positive Spearman correlation was found between the two intake estimates (p-value = 8×10⁻³; ρ=0.11).From the estimated intake of AA from food frequency questionnaires a significance was found for the 15-year-old children with higher AA adduct levels observed at higher consumption frequencies of fried potatoes/French fries. AA is considered a genotoxic carcinogen. For the estimated intake of AA for any age group and method (dietary recall or AA adduct), both a calculated margin of exposure as well as life-time quantitative cancer risk estimates, indicate health concern.A future study on food consumption designed with respect to AA exposure would provide a better understanding of the correlation between consumption and exposure and should give a more reliable estimate of the contribution of dietary AA to the overall cancer risk.